Women's experiences related to the 'great famine' in Ethiopia: A qualitative study. (November 2022) - Arage, Getachew; Belachew, Tefera; Abate, Kalkidan Hassen
Abstract: Background: In developing countries as women are mostly involved in handling food and feeding, their narrative is expected to generate optimal portrayal of the lived experiences surrounding the times of food shortage. Although there were repeated bouts of famine in Ethiopia, the experiences of women have never been documented. This qualitative study was aimed to explore and understand the experiences of women who survived the 1983-85 Ethiopian great famine. Method: A qualitative study was employed as an approach to document the experiences of women about the great Ethiopian famine in Kobo town of North Wollo Zone. In-depth interview and field notes lasting for an average of 40 min were carried out among 10 women who survived from the great famine. Purposive sampling technique was used to pick and interview women who had experience of Ethiopian great famine using local language. The interview was carried out using semi-structured interview guides with probes and open-ended questions to exhaustively capture the narratives. Texts with similar code were pooled together and presented in narratives using verbatims as illustrations. Data analysis was supported by ATLAS.ti 7.1.4 software. Members were checked with the congruence of given report and thematized results. Results: A total of four themes including perceived severity of the Ethiopian great famine, the consequences and causes the famine, common ailments during the famine, the coping mechanisms/survival strategies emerged after the data were saturated at ten in-depth interviews. The participants described that the famine was catastrophic and caused severe loss of human life. The heart touching findings such as a baby breastfeed her dead mother, eating non-food items such as wasted materials and wild plants, going without cloth on the road, mortgaging of farmland, and buried in the same ditch were reported by the famine survivors. Conclusion: The finding suggested a context-specific understanding of the Ethiopian great famine. It highlights the importance of further research to explore the long-term health and socio-economic impact of famine.